2003
DOI: 10.1167/iovs.02-0112
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the Horizontal Rectus Muscle Insertion Sites: Implications in Preoperative Assessment of Strabismus

Abstract: The results indicate good reliability and accuracy of US readings and suggest a potential usefulness in preoperative assessment of patients with strabismus with surgical failure and missing preoperative clinical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…As mentioned above, the insertions of the MR, IR, LR and SR in this study were located at 5.7 mm, 6.69 mm, 6.94 mm and 7.35 mm from the sclerocorneal limbus, respectively. Results of this study concurred with previous studies [1,8,18,19] and the original measurement by P.J. Tillaux which confirmed that the insertion of the MR was the closest one to the sclerocorneal limbus while the IR, LR and SR insertions progressively became further apart [4] (Table 6).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As mentioned above, the insertions of the MR, IR, LR and SR in this study were located at 5.7 mm, 6.69 mm, 6.94 mm and 7.35 mm from the sclerocorneal limbus, respectively. Results of this study concurred with previous studies [1,8,18,19] and the original measurement by P.J. Tillaux which confirmed that the insertion of the MR was the closest one to the sclerocorneal limbus while the IR, LR and SR insertions progressively became further apart [4] (Table 6).…”
Section: Discussionsupporting
confidence: 91%
“…Comparison of the extraocular muscles insertions [mm] from this study and from four previous studies[1,8,18,19] with…”
mentioning
confidence: 99%
“…Computerized tomography (CT), 2 cine-magnetic resonance imaging, 3 magnetic resonance imaging (MRI), 4 and conventional A-scan ultrasonography [5][6][7] have been used to determine the position of the extraocular muscle within the orbit, but none of these modalities can precisely determine the exact location. Previous studies 5,8 have shown that measurements taken using ultrasound biomicroscopy (UBM) could accurately determine the distances of insertion of the extraocular muscle from the limbus when applied both to unoperated horizontal muscles 8 and to horizontal muscles that had undergone prior surgery.…”
mentioning
confidence: 99%
“…5 The purpose of the present study was to evaluate the accuracy of UBM in measuring the distance (in mm) from the limbus to the insertion of vertical rectus muscles (superior rectus and inferior rectus) compared with the "gold standard" (surgical caliper) at the time of surgery. Tamburelli and colleagues 6 showed than conventional B-scan ultrasound can provide better visualization of the insertion site than CT or MRI, but exact measurement is not as accurate as with UBM. 5 The purpose of the present study was threefold: First to evaluate the accuracy of UBM in measuring the distance (in mm) from the limbus to the insertion of vertical rectus muscles (superior rectus and inferior rectus) compared with the "gold standard" (surgical caliper) at the time of surgery.…”
mentioning
confidence: 99%
“…Computed axial tomography, 2 magnetic resonance imaging (MRI), 3,4 cine MRI, 5 and conventional A and B scan ultrasonography 6,7 all have been used to study the size and position of the EOM. None of these modalities can accurately locate the insertion of the EOM to the globe and the insertion distance from limbus.…”
mentioning
confidence: 99%